COMPARATIVE STUDY OF SOME CONSTANTS IN DIFFERENT TYPES FROM OLIVE OIL PACKAGED IN GLASS BOTTLES - S. Al-Obady; U. Al-Jamaas; M. Al-Aswad (Mesopotamia Journal of Agriculture)
The present investigation was conducted to study four types of olive oil (Iraqi , Syrian,Turkish and Spanish) packed in glass bottles. The olive oil samples had been collected from local markets in Nineva province (Mosul city). The study aims at estimating and analyzing some of the factors affecting the quality of the oils , such as peroxide value, free fatty acids, refractive index, saponification value, relative density, and iodine value after storage in darkness for four months at 10, 20 and 30 ْC . The results showed a significant increasing in peroxide number during storage period in all types of olive oil . The oils stored at 20 and 30 ْ C provided the highest increase in peroxide number than those stored at 10 ْ C . The highest increase was noticed in Iraqi samples , Followed by Syrian , Turkish and Spanish, respectively . The results showed that the highest increasing of relative density and saponification value for oils were noticed at 30 ْ C . The figures were indicated increasing of free fatty acids percent with progress in storage period at 10 , 20 and 30 ْ C, and the relationship between refractive index with iodine number for Iraqi, Syrian , Turkish and Spanish of olive oil types .